Benefit Assessment of Pharmaceutical Products – a Critical Appraisal of Applied Methods - Porzsolt, F.; Braubach, P.; Huppertz, E.; Mühlbacher, A.; Otto, T.; Radic, D.; Schmidt, P.; Schulze-Solce, H.-N.; Clouth, J. (Gesundheitsökonomie & Qualitätsmanagement, 2012)
Scientists and politicians in all health care systems have not yet been able to agree on a uniformly accepted definition of the benefit of pharmaceutical products. Even if we cannot solve the problem we may contribute to understand it. To this end, we have compiled the methods used in various scientific disciplines to describe benefit and built a theoretical framework for these methods. The framework includes the aims, the subject matter measured, and the risks of a measurement as well as a possible sequence for the application of the methods as part of the benefit assessment. It includes six steps. Each of these steps contributes specific information to the benefit assessment. Because it is impossible to apply all of these steps and methods under real world conditions a sensible selection has to be made on which methods to consider or disregard. We assume that this selection depends on the selected objectives and the selection of objectives depends on values such as justice or utility. Consequently we propose to address as a first step the discussion about values before objectives can be defined and appropriate tools can be selected.
Keywords: benefit; utility; conjoint analysis; analytical hierarchy process; meta-analysis; structural equation model